2010
DOI: 10.1149/1.3269927
|View full text |Cite
|
Sign up to set email alerts
|

Film Breakdown and Anodic Dissolution during Stress Corrosion Cracking of Carbon Steel in Bioethanol

Abstract: The stress corrosion cracking (SCC) behavior of X-65 carbon steel was investigated in simulated fuel-grade ethanol (SFGE) using the slow strain rate test method, potentiodynamic polarization, electrochemical impedance spectroscopy, open-circuit potential, and potentiostatic current monitoring. Results indicate that crack initiation on carbon steel in the SFGE environment is associated with plastic deformation in the material, which leads to a surface film breakdown. The competition between active anodic dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 37 publications
1
22
0
1
Order By: Relevance
“…The SCC of carbon steel in ethanol has been proposed to occur by initiation by film breakdown, which is followed by crack growth controlled by a competition between anodic dissolution and repassivation 9, 16. No SEM observations have been previously published to support this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCC of carbon steel in ethanol has been proposed to occur by initiation by film breakdown, which is followed by crack growth controlled by a competition between anodic dissolution and repassivation 9, 16. No SEM observations have been previously published to support this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, there should be a zone of active steel surface near the crack tip and passivated oxide covered steel surface on the crack walls and outside the crack 9. Results from a recent study by Lou et al 16 indicated that the initiation of the SCC cracks is associated with plastic deformation in the steel, which leads to a surface film breakdown and to the propagation of the cracks controlled by the competition between active anodic dissolution and repassivation at the crack tip as proposed by Beavers et al 9. This may explain the effect of galvanic coupling to corroded steel increasing the susceptibility to SCC in FGE.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of different environmental parameters on the ethanol SCC are well known [2,[4][5][6][7][8][9][10][11][12][13][14][15][16], but the conditions within the ethanol SCC crack are still not known very well. One way to get information of the conditions within the SCC crack is to study the dissolution of the manganese sulfide inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Concluyeron que la probabilidad de aparición del fenómeno de la corrosión bajo tensión en los materiales ensayados, depende íntimamente del contenido en cloruros presentes en el etanol comercial. Lou et al [63] , estudiaron con detalle el mecanimo de corrosión de un acero al carbono en etanol. Observaron que, una vez iniciada la grieta, existe una competición entre la disolución anódica y la repasivación del sistema metá-lico, hecho que determina la velocidad de crecimiento de la grieta.…”
Section: Corrosión Bajo Tensión De Materiales Metálicos En Mezclas Deunclassified